ChemInform Abstract: A Catalytic Route to Dibenzodiazepines Involving Buchwald—Hartwig Coupling: Reaction Scope and Mechanistic Consideration. Issue 14 (March 2016) - Peixoto, Daniela; Locati, Abel; Marques, Carolina S.; Goth, Albertino; Ramalho, J. P. Prates; Burke, Anthony J.
Abstract: The key step of the title synthesis is Pd‐catalyzed C—N coupling of o‐bromoaldimines with o‐bromoanilines.